Analysis of Farmers’ Perceptions in Cadaskertajaya Village, Karawang, Regarding Extension Services on Agricultural Land Optimization - Ana Melani; Fatimah Azzahra; Wildan Ishananto (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2026)
Optimal land use is a very important aspect. Extension is a strategy and a gateway to information regarding the latest agricultural techniques, the use of technology, and the dissemination of information that can support land optimization efforts. It is undeniable that extension plays a vital role in enabling farmers to be exposed to new information or innovations, become interested in such innovations, and be motivated to apply the new information or innovations they have received. It is important to understand the cognitive, affective, and psychomotor perceptions regarding agricultural land optimization extension so that this study can deeply explore the community’s acceptance of land optimization information. The research method employed a quantitative approach, with 20 respondents who actively participated in extension activities. The research location was Cadaskertajaya Village, Karawang Regency. The analysis technique used the Likert scale and the effectiveness formula. The results of the study indicate that the farmer group’s perceptions of agricultural land optimization extension fall into the “very good” category, with an average rating of 3.49. The cognitive aspect received a rating of 3.54, placing it in the “very good” category. The affective aspect received a rating of 3.39, also placing it in the “very good” category. The psychomotor aspect received a rating of 3.54, placing it in the “very good” category. The effectiveness of the extension program attended by members of the farmers' group, as perceived in cognitive, affective, and psychomotor terms, falls into the “fairly effective” category.